Hydroethanolic Extracts of Leaves Possess Antimalarial Effects and Reverses Haematological and Biochemical Pertubation in -infected Mice - Francis O. Atanu; Damilare Rotimi; Omotayo B. Ilesanmi; Jamila S. Al Malki; Gaber E. Batiha; Precious A. Idakwoji (SAGE Publishing, 2022)
The current work investigated the chemical profile, antimalarial potential and capacity of hydroethanolic Senna alata extract (SAE) to reverse hematological and biochemical pertubation in Plasmodium berghei infected mice. Results of the phytochemical analysis revealed the presence of alkaloids, flavonoids, phenolics, tannins, terpenoids, saponins, steroids and cardiac glycosides. Total phenolic and flavonoid content was estimated to be 45.29 ± 2.34 mg GAE/g and 25.22 ± 2.26 mg QE/g respectively. In vitro analysis of the extract also confirmed its antioxidant property. Results of the test for prophylaxis of P. berghei indicated that SAE suppressed parasitemia significantly in treated groups in a dose dependent manner when compared with negative control group. Similarly, SAE improved the mean survival time (MST) and packed cell volume (PCV) of infected mice. The test for curative effect showed that SAE significantly suppressed parasitemia to 4.50 ± 1.05% compared to untreated group 29.83 ± 3.49%. Results of liver and kidney functions indices of treated animals indicated that whereas infection with P. berghei caused increase in the levels of AST, ALT, ALP, urea and creatinine, treatment with SAE significantly reversed the perturbation. Similarly, infected mice were dyslipidemic with concomitant increased activity of HMG CoA reductase and decreased activity of antioxidant enzymes with increase in lipid peroxides levels. However, these alterations were significantly reversed by administration of SAE. Results of this study shows that Senna alata possess antimalarial activity and therefore justify the traditional use of plant for the treatment of malaria.